Performance Of 3-Phase Induction Motor With Active Power Filter - Muhammad Taufiq Bin Tahreb, Muhammad Taufiq (2010)
The purpose of this project is to perform research regarding the design of active power filter which will affectively mitigate the harmonics in the ac lines connected with a 3-phase induction motor load.